Grammatical Errors on Final Paper Abstracts Composed by Students of Pharmacy Diploma - Atur Semartini (Universitas Sarjanawiyata Tamansiswa, 2024)
English has become one of the most important languages used globally. To produce effective sentences in English, EFL learners, such as in Indonesia, must master English grammar. However, the differences of grammar in English and Bahasa cause EFL learners to often produce grammar errors. Even though technology is increasingly developing and translator machines can assist students in writing English, grammar errors are still found. This research aims to investigate grammatical errors produced by Pharmacy Diploma students on their final paper abstracts. This research is a descriptive study. Data was obtained from 30 final paper abstracts of students of Pharmacy Diploma at Sekolah Tinggi Ilmu Kesehatan (STIKES) Nasional. The abstracts were taken randomly from the library of STIKES Nasional. Data was analyzed using Surface Structure Taxonomy by Dulay, Burt, and Krashen. The results of the analysis discovered 154 grammar errors. The dominant errors were Omissions with the number of errors is 54 errors (35,1%), followed by 44 errors of Additional (28,6%), 42 errors of Misformation (27,3%), and lastly, 14 errors of Misordering (9,1%). The results of this research imply that teachers and institutions need to prepare learning materials that can minimize errors made by students in the future